Solid Organ Transplantation From Deceased Donors With Infective Endocarditis: The UK Experience. Issue 3 (21st April 2021) - Greenhall, George H. B.; Robb, Matthew L.; Brown, Chloe; Johnson, Rachel J.; Tomlinson, Laurie A.; Callaghan, Chris J.; Watson, Christopher J. E.
Abstract : Background: There is little evidence regarding the use of organs from deceased donors with infective endocarditis. We performed a retrospective analysis of the utilization, safety, and long-term survival of transplants from donors with infective endocarditis in the United Kingdom. Methods: We studied deceased donor transplants over an 18-y period (2001–2018) using data from the UK Transplant Registry. We estimated the risk of infection transmission, defined as a microbiological isolate in the recipient matching the causative organism in the donor in the first 30 days posttransplant. We examined all-cause allograft failure up to 5 years in kidney and liver recipients, comparing transplants from donors with endocarditis with randomly selected matched control transplants. Results: We studied 88 transplants from 42 donors with infective endocarditis. We found no cases of infection transmission. There was no difference in allograft failure between transplants from donors with infective endocarditis and matched control transplants, among either kidney (hazard ratio, 1.48; 95% CI, 0.66-3.34) or liver (hazard ratio, 1.14; 95% CI, 0.54-2.41) recipients. Compared with matched controls, donors with infective endocarditis donated fewer organs (2.3 versus 3.2 organs per donor; P  < 0.001) and were less likely to become kidney donors (odds ratio, 0.29; 95% CI, 0.16-0.55). Conclusions: We found acceptable safety and long-term allograft survival in transplants from selected donors with infective endocarditis in the United Kingdom. This may have implications for donor selection and organ utilization.